1993
DOI: 10.1103/physrevb.48.12732
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic circular x-ray dichroism in Ce intermetallic compounds

Abstract: Magnetic circular x-ray dichroism (MCXD) studies at L2 3 absorption edges in intermediate-valence (IV) compounds CeFez, Ce(Feo sCop g)2 CeCo"CezCo, 7, and trivalent 4f ' systems (CeRuzGe2, Ce3A1», CePd, CeFe2H3 8) at the Ce L2 3 edges are presented. The comparison with reference compounds (La, Lu, Hf, Cxd) confirms the existence, in such IV systems, of an ordered Sd magnetic moment on the Ce site antiferromagnetically coupled with the 3d Fe (Co) moment. Moreover, this study suggests, provided the 4f orbital m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 33 publications
8
57
1
Order By: Relevance
“…The T C = 230 K is almost lower by a factor of 3 as compared to that of LuFe 2 ͑T C = 610 K͒ with its full 4f shell and YFe 2 ͑T C = 545 K͒, which has no 4f electrons. 2,4 The saturation magnetic moment is also anomalously low ͑M s = 2.4 B / f.u.͒ as compared to that of LuFe 2 ͑M s = 2.9 B / f.u.͒. 2,4 Another interesting observation in CeFe 2 is the occurrence of antiferromagnetic fluctuations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T C = 230 K is almost lower by a factor of 3 as compared to that of LuFe 2 ͑T C = 610 K͒ with its full 4f shell and YFe 2 ͑T C = 545 K͒, which has no 4f electrons. 2,4 The saturation magnetic moment is also anomalously low ͑M s = 2.4 B / f.u.͒ as compared to that of LuFe 2 ͑M s = 2.9 B / f.u.͒. 2,4 Another interesting observation in CeFe 2 is the occurrence of antiferromagnetic fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 The saturation magnetic moment is also anomalously low ͑M s = 2.4 B / f.u.͒ as compared to that of LuFe 2 ͑M s = 2.9 B / f.u.͒. 2,4 Another interesting observation in CeFe 2 is the occurrence of antiferromagnetic fluctuations. 1 It has been reported that substitution of small amounts of elements such as Co, Al, Ru, Ir, Os, and Re stabilizes the low-temperature dynamic AFM phase in CeFe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Lu-Fe intermetallic compound, Lu atoms may possess a non-intrinsic, induced magnetic moment originating from the hybridization effects of 5d-Lu states with the 3d states of magnetic transition metal matrix (see, e.g., theoretical and experimental results on LuFe 2 [36,37]). Because the L 2 , 3 XMCD signals are directly related to the spin polarization of the d final states (and determined by the selection rules) and act as a spin detector of the absorbing atom, the data in Fig.…”
Section: B Lutetium L Iiiii -And Ruthenium L Ii -Edge Xanes and Xmcmentioning
confidence: 99%
“…A small DOS peak in the vicinity of E F is mostly of a spin-down character and is caused by the 12k and 6g atomic Fe positions (i.e., those in close proximity with Ru atoms), both having sharp edges in the p-DOS at the Fermi energy. 094420-7 [36,37]. A smaller average Lu moment is derived from the XMCD data at the maximum applied magnetic field of 3 T, M Lu = −0.072 μ B .…”
Section: Electronic-structure Calculationsmentioning
confidence: 99%
“…XAS at the L2,3 (ROhler, 1987) and lVh,5 (Kaindl, 1985) edges has been widely performed to study the electronic properties of rare earths (4f occupancy using phenomenological interpretation of the edge profiles (ROhler, 1987), or magnetism using X-ray Magnetic Circtflar Dichroism (XMCD) (Finazzi, 1995, Giorgetti, 1993, Kaindl, 1985. Resonance experiments are a new way to assign the main structure of the absorption edge to precise final electrolfic configurations, for relatively localized states.…”
Section: Abstract : Resonant Photoemission Resonant Auger Cerium Imentioning
confidence: 99%